The Influence of Service Quality, Promotion and Price on the Decision to Purchase Seafood Products at PT Jaya Hasil Laut Medan - Adam Afiezan; Denny Wijaya; Vivi Cresia; Hendri Hendri (Institute of Computer Science (IOCS), 2020)
This research was conducted at PT Jaya Seafood. The purpose of this study was to examine the effect of Service Quality, Promotion and Marine Product Decisions on PT Jaya Hasil Laut. The approach in this study is a quantitative approach. The expected population is 194 customers and the sample in this study is 131 customers. The research method used is multiple linear regression analysis. Service Quality, Promotion and Prices simultaneously and partially have a positive and significant effect on the Marine Product Purchase Decision at PT Jaya Hasil Laut